Exploring factors affecting nurse anxiety in Northwest Ethiopia: a multicenter study - Misganaw, Adane; Hailu, Mignot; Bayleyegn, Gashachew; Aderaw, Mekidem; Yigzaw, Zeamanuel Anteneh; Alemu, Tihtna; Asmare, Lakew (Frontiers in Psychiatry, 2024)
Introduction Anxiety is a commonly reported mental health disorder that significantly contributes to the global burden of disease. However, proper counseling, problem-solving strategies, and promotion of healthy lifestyle practices have a positive effect on reducing nurse anxiety, but there is limited evidence in Ethiopia, particularly in this study area. Therefore, this study aimed to assess the prevalence and identify factors affecting nurse anxiety in Northwest Ethiopia’s comprehensive specialized hospitals. Methods An institution-based cross-sectional study was conducted among 746 study participants from April 14 to May 20, 2023. A simple random sampling technique was used. An interviewer-administered questionnaire was used. Data were entered into EpiData version 4.6.0 and exported to STATA version 17 for analysis. In binary logistic regression, variables with a p-value of less than 0.25 were considered candidates for multivariable logistic regression. An association was declared at a p-value of less than 0.05 with a 95% confidence interval. Result In this study, the prevalence of anxiety was 33.9%. Thus, being female [adjusted odds ratios (AOR) = 1.53, 95% CI = 1.08, 2.22], working in an emergency department (AOR = 3.65, 95% CI = 1.83, 7.28), working night duty shifts (AOR = 3.12, 95% CI = 2.19, 4.46), having conflict with coworkers (AOR = 1.7, 95% CI = 1.14, 2.51), and having poor social support (AOR = 2.13, 95% CI = 1.23, 3.69) were variables significantly associated with anxiety. Conclusion This study revealed that one-third of nurses experienced anxiety, which is a critical indicator of mental health within this population. Important factors that were found to be significantly associated with anxiety include being female, working in the emergency department, having a conflict with coworkers, having poor social support, and working night duty shifts. These findings show the need for the implementation of counseling services and the adaptation of effective coping strategies for nurses working at comprehensive specialized hospitals. Understanding the impact of anxiety on nurses is important to design interventions aimed at improving their mental health and job satisfaction.